Handbook of the protists - Archibald, John M.; Simpson, Alastair G. B.; Slamovits, Claudio H. (Springer, 2017)
Published in a modern, user-friendly format this fully revised and updated edition of 'The Handbook of Protoctista' (1990) is the resource for those interested in the biology, diversity and evolution of eukaryotic microorganisms and their descendants, exclusive of animals, plants and fungi. With chapters written by leading researchers in the field, the content reflects the present state of knowledge of the cell and genome biology, evolutionary relationships and ecological/medical/economic importance each major group of protists, organised according to current protist systematics as informed by molecular phylogenetics and genomics.- Resumé vydavatel
Keywords: Prostista; mikrobiologie; parazitologie; prostists; microbiology; parasitology; elektronické knihy; příručky; electronic books; handbooks and manuals